How Start-up Ecosystem and Public Administration Support Entrepreneurs in Surviving the Valley of Death - Sutarjo*, Sutarjo; Bajuri, Diding (Universitas Syiah Kuala, 2024)
This paper provides the discussion on how start-up ecosystem and public administration play important role in helping start up to survive Valley of Death. Most startups do not advance beyond the early stage of development and face challenges of sustainability and enter the valley of death. Within an ecosystem there is sufficient proximity between key actors so that fast progress is possible. Mentorship that combines business, tech, and health can be very helpful. Startups need to collaborate with their stakeholders such as academic and research institutes and people with relevant know-how and business skills. Government support through public policy making is important to bridge the entrepreneur into ecosystem. Policy should provide a better business environment or infrastructure, allocate more funds for commercialization of innovations, construct facilities for entrepreneur and tax breaks for new and striving businesses.